2014
DOI: 10.1111/jam.12601
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of a BSL3 laboratory by hydrogen peroxide fumigation using three different surrogates for Bacillus anthracis spores

Abstract: The results of this study provide important results in the field of hydrogen peroxide decontamination when analysing the effect on spores other than those of G. stearothermophilus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 30 publications
(84 reference statements)
0
24
0
Order By: Relevance
“…Survival of Geobacillus stearothermophilus spores was used to verify the disinfection efficiency of VHP in this study [11]. The effects of different injection rates and different injection times were investigated to determine optimal disinfection conditions.…”
Section: Determination Of Optimal Disinfection Conditions Using Vhpmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival of Geobacillus stearothermophilus spores was used to verify the disinfection efficiency of VHP in this study [11]. The effects of different injection rates and different injection times were investigated to determine optimal disinfection conditions.…”
Section: Determination Of Optimal Disinfection Conditions Using Vhpmentioning
confidence: 99%
“…VHP can automatically degrade into water and oxygen in nature, and therefore is friendly to the environment. Hydrogen peroxide decontamination systems are widely used to reduce the risk of infection in hospitals, biosafety laboratories, and so on [10,11]. Chou et al demonstrated that hydrogen peroxide had no effect on the mechanical properties of nylon, polyester, and Nomex [12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, surrounding rooms have to be closed during the procedure. Furthermore, formamide forms toxic or irritant residues on surfaces, which subsequently need to be cleaned (Cheney and Collins, 1995;Krishnan et al, 2006;Gordon et al, 2012;Kaspari et al, 2014). Finally, since 2014, formamide is classified as a Class 1B carcinogen and Class 2 mutagen in Europe and has also been recognized as a human carcinogen in the United States (U.S Department of Health and Human Services, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it has become more widely used than formamide for room-wide decontaminations in recent years. It has proven to be effective against a wide range of bacteria, spores, and viruses in various facility settings (Heckert et al, 1997;Krishnan et al, 2006;Pottage et al, 2010;Bentley et al, 2012;Goyal et al, 2014;Kaspari et al, 2014;Lemmen et al, 2015;Petit et al, 2017). Depending on the environmental conditions, H 2 O 2 can react as a weak acid, a potent oxidizing, or a reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we describe a comprehensive, systematic method of facility-wide C. bovis eradication. All murine housing rooms; use, quarantine, storage, common procedural, surgical, imaging, genetic engineering, and pharmacy areas; and offices of the facility were decontaminated by using VHP (Bioquell, Horsham, PA) with room equipment left in place; this process was verified through the use of biologic and chemical indicators applied in healthcare, 1,11,15,16 biocontainment, 9 and animal facilities. 10,17 In addition, decontamination of surfaces, including benchtops, biosafety cabinets, animal transfer stations, gloved hands, imaging and anesthesia equipment, and the external surfaces of the occupied IVC before and after each use was accomplished by treatment with accelerated hydrogen peroxide (aHP) typically used in healthcare settings and validated as an effective, safe sanitizing agent (OxivirTb, Diversey, Charlotte, NC).…”
mentioning
confidence: 99%